THE EFFECTIVENESS OF THE PROHIBITION OF THE CODE OF ETHICS ON SELF-PROMOTION OF NOTARIES AND ITS IMPACT ON NOTARY PRACTICE IN INDONESIA - Hikmawati, Cahya Agustianing Durrah; Ardini, Sofia; Ma'arif, Malika Syaifina Al; Arsyta, Nabila (Awang Long Law Review, 2025)
The Code of Ethics for Notaries in Indonesia strictly prohibits notaries from conducting self-promotion in any form, as regulated in the Notary Position Law and the Code of Ethics for Notaries of the Indonesian Notary Association (INI). This prohibition aims to maintain professionalism, neutrality, and integrity in notarial practice. However, in this digital era, the prohibition is a challenge, especially for novice notaries who have difficulty getting clients. This study analyzes the effectiveness of the prohibition of self-promotion against Notaries, the factors that influence it, and how it impacts notary practice in Indonesia. The research method used in this study is a normative legal research method conducted using a legal material collection approach through library research techniques. The results of this study show that although basically self-promotion of Notary is necessary for a Notary in supporting his profession, he must still pay attention to the professional ethics of the position he holds in order to maintain professionalism, neutrality, and integrity in accordance with the provisions in the Notary Position Law and the Notary Code of Ethics so that he is prohibited from conducting publication or self-promotion, either alone or together, by stating his name and position.